Variasi Ortografi dan Praktik Textese dalam Komunikasi WhatsApp Penutur Muda di Aceh Tamiang: Kajian Sosiolinguistik Siber - Indah Fajarini; Tanita Liasna; Widia Tamara; Rico Adriansyah (Hasta Wiyata, 2026)
This study aims to describe the forms and functions of orthographic variation in WhatsApp communication among young speakers in Harum Sari Village, Aceh Tamiang, and to examine its relation to textese practices within the ecosystem of Computer-Mediated Communication (CMC). This research employed a qualitative descriptive approach from the perspective of cyber sociolinguistics. The data were obtained through screenshot documentation, exported WhatsApp conversations, and questionnaires distributed to 24 purposively selected respondents. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldana through the stages of data condensation, data display, and conclusion drawing. The findings reveal that digital orthographic practices among young speakers in Harum Sari are dominated by five major patterns: contraction and vowel ellipsis, cyber acronyms and initialisms, graph substitution using numbers, visual onomatopoeia, and expressive logograms. These variations do not merely represent spelling deviations, but also function as communicative strategies intertwined with principles of linguistic economy, relational closeness, emotional expression, and group solidarity in digital spaces. The findings further indicate that WhatsApp language operates within the logic of Language of Immediacy, in which written language moves closer to the spontaneity of spoken interaction. This study argues that digital orthographic variation should be understood as a linguistic practice emerging from the negotiation between communicative efficiency, social identity, and the digital literacy culture of younger generations.